"As Old as Man": Helena Blavatsky's Pagan Perennial Philosophy. (31st December 2020) - Chajes, Julie
Abstract : This paper explains the perennialist doctrines of Helena Blavatsky (1831–1891), the main theorist of Theosophy, a form of occultism whose heirs include New Age and contemporary Pagan spirituality. The analysis is restricted to her first major work, Isis Unveiled (1877). In that treatise, Blavatsky argued that a single Pagan tradition lay at the basis of all historical religions and that this ancient wisdom had been corrupted by the Catholic and Protestant churches to gain power over the blind masses. Providing a fine-grained understanding of such influential heterodox perspectives of the nineteenth century, the article contributes to a historicization of religious universalism and other ideas that have become popular in modern and post-modern times, such as the claim that a perennial "mysticism" lies at the heart of all "true spirituality, " the idea that "spirituality" is something different from "religion, " and the theory that monotheism is an inherently intolerant form of religion whereas mystical, Pagan, or polytheistic spiritualities are inherently peaceful.